Squirrels leap, squirrels sleep - Sayre, April Pulley (Henry Holt and Company, 2016)
"Squirrels wrestle. Squirrels leap. Squirrels climb. Squirrels sleep. If you followed a squirrel for a day, what would you see? Climbing branches, storing seeds, making homes in tree holes, and maybe even flying! [The creators of this book offer] a glimpse into this fascinating world. Discover different kinds of squirrels as the scamper, eat, and--finally--sleep."--Amazon.com.